Issues of Regulation of Land Relations in Uzbekistan - A.S. Chertovitsky; Sh.K. Narbaev; B.M.Uspankulov (Zien Journals, 2023)
The issues of land management in the Republic of Uzbekistan were studied. It has been established that this problem includes two components: state regulation of land relations and administrative and departmental management at the regional and district territorial levels, their specific content is determined when creating a land market in the republic. The forms of manifestation of land relations as an integral part of the production relations of society, their features are systematized.
Keywords: Land; property; private; land lease